The influence of electromyographic biofeedback therapy on knee extension following anterior cruciate ligament reconstruction: a randomized controlled trial - Christanell, F.; Hoser, C.; Huber, R.; Fink, C.; Luomajoki, H. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2012)
Background: Loss of knee extension and a deficit in quadriceps strength are frequently found following anterior cruciate ligament (ACL) reconstruction. The aim of this study was to investigate whether the addition of Eletromyographic Biofeedback (EMG BFB) therapy for the vastus medialis muscle to the in the early phase of the standard rehabilitation programme could improve the range of knee extension and strength after ACL reconstruction more than a standard rehabilitation programme. The correlation between EMG measurement and passive knee extension was also investigated.